Mối quan hệ giữa nhận thức, sự tham gia trách nhiệm xã hội doanh nghiệp và vốn tâm lý của nhân viên: Vai trò điều tiết của bản sắc đạo đức - Nguyễn Hồng, Quân; Hà Phương , Thảo; Lê Đức , Duy; Đoàn Thị Thu , Hương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Based on social exchange theory and social identity theory, this study aims to investigate the impact of Corporate Social Responsibility (CSR) perception and CSR participation on employees' PsyCap and the moderating role of moral identity. By using data collected from an online survey with 500 employees working at enterprises implementing CSR in Hanoi and employing structural equation modeling (SEM) analysis, the research result shows that both CSR perception and CSR participation of employees have positive impacts on PsyCap as well as affirms the moderating effect of moral identity. In addition, the positive impact of CSR participation on CSR perception is also a finding of this study. Policy implications for businesses and the state to raise a perception, participation in CSR activities, and moral orientation of employees are provided.
Keywords: Corporate Social Responsibility; CSR Perception; CSR Participation; PsyCap; Moral Identity